PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DAN GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Prasetyowati, Agustin; Marsono, Marsono (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of disclosure of sustainability reports on the economic dimension, social dimension, environmental dimension, and green accounting on the company's financial performance. The population of this study amounted to 165 manufacturing companies listed on the IDX in 2018-2022. Sample selection was carried out using the purposive sampling method with the results of 33 research samples. The data analysis method used is multiple linear regression analysis. Based on the results of the study, the disclosure of the economic dimension sustainability report does not affect return on assets (ROA) and return on sales (ROS). The disclosure of the social dimension sustainability report has a significant positive effect on ROA and ROS. Disclosure of the environmental dimension sustainability report does not affect ROA and has a significant positive effect on ROS. Furthermore, green accounting has a significant positive effect on ROA and does not affect ROS.